Copper‐Catalyzed Stereoselective Defluorinative Borylation and Silylation of gem‐Difluoroalkenes. Issue 5 (23rd January 2018) - Tan, Dong‐Hang; Lin, E; Ji, Wei‐Wei; Zeng, Yao‐Fu; Fan, Wen‐Xin; Li, Qingjiang; Gao, Hui; Wang, Honggen
Abstract: The copper‐catalyzed stereoselective defluorinative borylation and silylation of gem ‐difluoroalkenes was developed. The protocol led to the exclusive formation of Z type monofluoroalkenyl borons and silanes in generally good efficiency with broad substrate scope. The products formed could be readily transformed to other F‐containing molecules by taking advantage of the versatile reactivities of C−B and C−Si bonds. Experimental and theoretical mechanistic studies were conducted which support an olefin insertion/ syn ‐planar β‐F elimination pathway. Abstract :